Suomalainen taidegalleria : Albert Edelfelt, Akseli Gallen-Kallela, Juho Rissanen, Helena Schjerfbeck, Hugo Simberg - Kämäräinen, Eija; Hilpo, Seppo; Edelfelt, Albert; Gallen-Kallela, Akseli; Rissanen, Juho; Schjerfbeck, Helene; Simberg, Hugo (WSOY, 1999)
English summaries.
Keywords: Edelfelt, Albert; Gallen-Kallela, Akseli; Rissanen, Juho; Schjerfbeck, Helene; Simberg, Hugo; maalaustaide; taidemaalarit